Role of androgenic deprivation on the contractile response to norepinephrine in vas deferens isolated from rats submitted to swimming-stress - Carlos, C. P. [UNESP]; Padovani, C. R. [UNESP]; Pereira, O. C M [UNESP] (My University, 1995)
The effects of androgenic deprivation induced by castration on the norepinephrine contractile response of vas deferens from rats, which have been submitted to acute swimming-stress were determined. Acute swimming-stress led to subsensitivity to norepinephrine in vas deferens excised from intact rats. Similarly, castration also induced subsensitivity to norepinephrine, but no further subsensitivity occurred in organs from castrated rats submitted to acute stress. The results indicate a different response to norepinephrine in terms of relative responsiveness ratio, when vas deferens was excised from castrated rats or castrated rats submitted to acute stress. It is suggested that androgenic steroids modulate the recovery of homeostasis in rat vas deferens during acute stress, and that this effect may involve mechanisms that affect both the sensitivity of adrenergic receptors and the system of neuronal uptake of catecholamines.
Keywords: castration; exertion; norepinephrine; rats, inbred strains; stress; vas deferens; adrenergic receptor; androgen; noradrenalin; animal experiment; homeostasis; ligation; male; muscle contraction; nonhuman; rat; swimming